Impact of agrarian land use and land cover practices on survival and conservation of nilgai antelope (Boselaphus tragocamelus) in and around the Abohar wildlife sanctuary, northwestern India. Issue 3 (3rd July 2019) - Bajwa, Parteek; Chauhan, Netrapal Singh
ABSTRACT: There is an information gap on biodiversity effects of land use and land cover (LULC) dynamics of agrarian landscapes. Such data are essential for policy making and species management in agro-ecosystems. Thus, changes in LULC inside the Abohar wildlife sanctuary and its eco-sensitive zone were investigated using LISS-III satellite images from 2003 to 2016. The area under cropland witnessed a 3.6% increase, whereas wastelands significantly declined by 4.3%. Further, the impact of LULC dynamics on nilgai ( Boselaphus tragocamelus ) was determined through mortality distribution in the sanctuary from 2012 to 2017. The spatio-temporal distribution pattern of mortality revealed that a total of 336 nilgai died during the six years studied. Free-ranging feral dogs, in conjunction with fencing and road accidents, were the major factors involved in nilgai casualty. Fatalities were clustered in regions with significant LULC change. The results confirmed that intensified development and reuse of derelict agricultural fields disturbed nilgai ecology and habitat use pattern. Human-wildlife conflicts in agrarian landscapes are an increasing concern and should be managed following identification of sensitive areas.